Establishing an in vivo large animal model of one-lung ventilation and operative lung trauma - Catherine Giffin; Jay Kormish; Martha Hinton; Shyamala Dakshinamurti; Ruth Graham; Biniam Kidane (PLoS ONE, 2025)
Background Respiratory complications, including acute lung injury (ALI) and acute respiratory distress syndrome (ARDS), are important causes of morbidity and mortality among lung surgery patients. Lung surgery introduces surgical and atelectatic trauma to the operated lung, while one-lung ventilation (OLV) applied to the contralateral lung is also a suspected mechanism of ventilator-induced lung injury (VILI). Our goal was to develop a large animal model to assess the relative lung injury induced by surgical and ventilator trauma during left upper lobectomy in juvenile pigs. Methods Sixteen pigs (24–32 kg) were randomly assigned to one of three OLV exposure groups. The control group (n = 5) was exposed to lung-protective ventilation (LPV) during OLV, the second group (n = 5) was exposed to potentially injurious ventilation (IMV) during OLV using higher tidal volume and peak airway pressure and the third group (n = 6) was exposed to hyperoxia with protective ventilation (LPV-HO) for the duration of OLV and surgery. Findings We describe the surgical and ventilation methods for a successful lung surgery pilot for a porcine OLV model. Initial surgeries show that our protocol is effective in reproducibly maintaining peak airway pressures, tidal volumes and oxygen delivery according to the parameters of LPV, IMV and hyperoxia during OLV. Bronchoalveolar lavage fluid IL-6 was elevated in response to IMV during OLV, hyperoxia and surgical exposure. Conclusions We describe a reproducible protocol for an in vivo large animal model of OLV lung surgery with a protective and two injurious mechanical ventilation arms with collection of physiologic data and biospecimens.